Clinical Challenges in Primary Erythromelalgia: A Real-Life Experience from a Single Center and a Diagnostic-Therapeutic Flow-Chart Proposal - Michelerio, Andrea; Tomasini, Carlo; Arbustini, Eloisa; Vassallo, Camilla (Dermatology Practical & Conceptual, 2023)
Introduction: Primary erythromelalgia (EM) is a rare clinical syndrome characterized by recurrent erythema, burning pain and warmth of the extremities. The symptoms greatly compromise the patients' quality of life leading to severe disability. SCN9A mutations can be the cause of the disease. Dermatologists are often the specialists these patients turn to for assistance.Objectives: To describe the demographic and clinical characteristics of patients with primary EM, to assess the presence and mutation types in the SCN9A gene, to evaluate the effectiveness of several therapeutic approaches, and to propose a diagnostic algorithm with therapeutic implications.Methods: A monocentric retrospective study using the database of patients with a discharge diagnosis of primary EM of our Center. Demographic, clinical, instrumental and laboratory data of patients were reviewed.Results: Eleven female patients (age range 16 to 57) were selected. All patients were affected in both the lower and upper extremities. Follow-up ranged from 2 to 9 years. Four patients had four different heterozygous variants of the SCN9A gene. Two patients, although genetically negative, had a suggestive family history. A variety of medications were tried in all our patients to alleviate symptoms, but their efficacy was variable, partial and/or transitory. The most effective therapies were antihistamines, venlafaxine, and mexiletine.Conclusions: The diagnosis and treatment of EM remain challenging. Patients with this condition display a wide spectrum of clinical manifestations and severity, as well as a paucity of resources and structures to support them. Mutations in the SCN9A gene are not always detected.